2021
DOI: 10.1371/journal.pone.0257418
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress modulates polymorphonuclear cell response in early pregnancy cows: I. interferon pathway and oxidative stress

Abstract: One of the major causes of early pregnancy loss is heat stress. In ruminants, interferon tau (IFNT) is the embryo signal to the mother. Once the interferon signaling pathway is activated, it drives gene expression for interferon-stimulated genes (ISGs) and alters neutrophils responses. The aim of the present study was to evaluate interferon (IFN) pathway, ISGs and gene expression in polymorphonuclear leukocytes (PMN) and oxidative stress in dairy cows under heat stress. Pregnant cows had their estrous cycle sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…A possible explanation for these results relies on the negative environmental impact of heat stress and the presence of higher humidity in the environment on fertility, which has been previously reported (Astiz and Fargas, 2013;Schüller et al, 2016). Heat stress reduces oocyte quality, compromises the uterine environment, and alters ovarian function, which is detrimental to embryonic development (Wolfenson and Roth, 2019;Amaral et al, 2021). Additionally, humidity in the environment deteriorates the general health of the cows, increasing their risk of suffering metritis and endometritis and thus compromising fertility (Adnane et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…A possible explanation for these results relies on the negative environmental impact of heat stress and the presence of higher humidity in the environment on fertility, which has been previously reported (Astiz and Fargas, 2013;Schüller et al, 2016). Heat stress reduces oocyte quality, compromises the uterine environment, and alters ovarian function, which is detrimental to embryonic development (Wolfenson and Roth, 2019;Amaral et al, 2021). Additionally, humidity in the environment deteriorates the general health of the cows, increasing their risk of suffering metritis and endometritis and thus compromising fertility (Adnane et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Mammalian CL contains two types of steroidogenic cells, designated as small and large luteal cells ( Al-Gubory et al, 2012 ). Although, the mechanisms of cell death and maintenance of progesterone production are complex and vary among mammalian species, it has been suggested that antioxidants play a significant role in CL during estrous cycle ( Al-Gubory et al, 2005 , 2006 ; Sugino, 2006 ; Amaral et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The production and propagation of reactive oxygen species (ROS) by CL depends on several regulatory factors, such as luteal antioxidants, steroid hormones, and cytokines ( Al-Gubory et al, 2012 ; Amaral et al, 2021 ). However, the factor that has the greatest contribution to CL function is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations